A hierarchically porous bioactive glass-ceramic microsphere with enhanced bioactivity for bone tissue engineering. Issue 10 (July 2019) - Hong, Wei; Guo, Fangwei; Hu, Li; Wang, Xin; Xing, Chen; Tan, Yu; Zhao, Xiaofeng; Xiao, Ping
Abstract: A hierarchically porous bioactive glass-ceramic microsphere with enhanced bioactivity and good biocompatibility was fabricated via electro spraying technique assisted with non-solvent induced phase inversion. The electro sprayed bioactive glass (ESBG) microspheres were 20 ± 5 μm in diameter, and composed of four characteristic pores: <200 nm, 200–500 nm, 500–1000 nm and >1000 nm. The influences of sintering temperatures (600 °C-1000 °C) on the microstructure, crystalline phase and the related in vitro bioactivity of the samples were investigated. All the ESBG microspheres possessed bioactivity, and the earliest apatite deposition time (3 h) occurred in the samples sintered at 1000 °C owing to the highly porous structure and the formation of wollastonite. The in vitro cytotoxicity was evaluated via CCK-8 assay using MC3T3-E1 cells, revealing the good biocompatibility as well. These results suggest that the ESBG microsphere is a promising material for bone tissue engineering.